Cryptic homoeology analysis in species and hybrids of genus Zea - Molina, María del Carmen (2013)
Cryptic intergenomic pairing of genus Zea was induced by the use of a diluted colchicine solution in order to elucidate the phylogenetic relations and differentiation of the homoeologous genomes. Results indicate that in species and hybrids with 2n = 20, there was chromosome pairing between the homoeologous A and B genomes with a maximum of 5IV, with the exception of Zea diploperennis and their interspecific hybrids where cryptic homoeologous chromosome pairing was not induced. In almost all 2n = 30 hybrids, observed cryptic pairing increased to a maximum of 10III although Z. mays × Z. mays with 2n = 30 did not show significant differences between treated and untreated materials. Pairing was also observed in species and hybrids with 2n = 40, in which a maximum of 10IV was observed, with the exception of Z. mays with 2n = 40 where treated and untreated cells did not differ significantly.